Puerperal women's satisfaction with the obstetric services received: improvement of an assessment instrument - Lourivaldo Bispo Alves Junior; Cristiane Faiad; Carlos Manoel Lopes Rodrigues; Ângela Ferreira Barros (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to improve an instrument that measures postpartum women's satisfaction with obstetric care. Methods: action research, developed from a preliminary version of an instrument prepared by nurse-midwives working in public services in the Federal District. The analysis of the results of application of instrument carried out in a pilot test, analysis of evidence of instrument validity, literature review, focus group with the instrument's developers and interview with the target audience were carried out. Results: factorial analysis showed three existing factors in the construct. Seven nurses participated, discussing the instrument reformulation, and 20 mothers reported their perceptions about the care received during childbirth, generating five thematic units. Final Considerations: instrument improvement occurred through item and response scale reconstruction and reorganization, in addition to application of a pre-test with the target population, resulting in an instrument composed of 13 items.